2017
DOI: 10.1002/hrm.21836
|View full text |Cite
|
Sign up to set email alerts
|

Strategic HR system differentiation between jobs: The effects on firm performance and employee outcomes

Abstract: The purpose of this research was to understand the extent to which firms apply different human resource management systems to different occupations within the same organization (HR differentiation), and how this influences both firm and employee outcomes. We conducted two studies pertaining to these questions. The first study was based on data collected from managers and the results showed that firms differentiate their HR investments based on the strategic value of occupations, which was further associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 73 publications
(106 reference statements)
3
57
0
2
Order By: Relevance
“…In 1987, Schuler and Jackson cited a list of human resource management (HRM) practices contained planning choices, 1.6. Dimensions of SHRM in this study Schmidt et al (2018) investigated the effect of SHRM system differentiation between jobs and found that a lower degree of HR system investment results in a higher turnover intention ration and lower level of organizational citizenship behavior among employees. Their study highlighted the importance of strategic value of human resource practices.…”
Section: Dimensions Of Shrm In the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In 1987, Schuler and Jackson cited a list of human resource management (HRM) practices contained planning choices, 1.6. Dimensions of SHRM in this study Schmidt et al (2018) investigated the effect of SHRM system differentiation between jobs and found that a lower degree of HR system investment results in a higher turnover intention ration and lower level of organizational citizenship behavior among employees. Their study highlighted the importance of strategic value of human resource practices.…”
Section: Dimensions Of Shrm In the Literaturementioning
confidence: 99%
“…Other researchers have confirmed this goal (Fottler 2002, Sareen 2018). On the other hand, some studies have indicated the strategic importance of human resource management practices (Schmidt et al 2018). This means that resource management practices differ in terms of their contribution to help the organization to achieve its strategic objectives.…”
Section: Relationship Between Shrm and Organizational Resiliencementioning
confidence: 99%
“…Investment in skill development or costly job redesign, for example, would be reserved for core or high-value employees (Schmidt et al, 2018). Confirming human capital assumptions based on HRM's competitive advantage, the adoption of skills-oriented HRM was more prevalent among organizations relying on high-skilled workforces.…”
Section: Discussionmentioning
confidence: 96%
“…However, there has been renewed scholarly attention on the impact of HRM on employee well‐being (Guest, ), especially given the intensified working environments brought on by recession. Growing evidence of HRM's potentially conflicting outcomes, for example, higher job satisfaction alongside poorer affective well‐being (Boxall et al, ; Wood et al, ), suggests we cannot assume all HRM practices are perceived positively by employees (Schmidt, Pohler, & Willness, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation